Multicomponent Selective Thioetherification of KSAc: Easy Access to Symmetrical/Unsymmetrical 4‐Alkylthio‐3‐halo‐2(5H)‐furanones. Issue 3 (24th February 2023) - Zhou, Yong‐Jun; Fang, Yong‐Gan; Yang, Kai; Yu, Shi‐Wei; Chen, Zu‐Jia; Wang, Bi‐Cheng; Zhan, Hai‐Ying; Wang, Zhao‐Yang
Abstract: An easy two‐/three‐component selective thioetherification of KSAc for the synthesis of a series of symmetrical/unsymmetrical 4‐alkylthio‐3‐halo‐2(5 H )‐furanones has been described. The reaction without any metal catalyst or additive is carried out in air atmosphere at room temperature for 5 h, only using potassium thioacetate as an odourless sulfur source and a base simultaneously. The broad substrate scope and high yield make it important for the studies on both constructing C−S bond based on non‐aryl Csp2 −X bond and synthesizing new 2(5 H )‐furanone functional molecules. Abstract : A transition metal‐free catalyzed synthesis of symmetrical/unsymmetrical 4‐alkylthio‐3‐halo‐2(5 H )‐furanones has been developed. The reaction without any metal catalyst or additive is carried out in air atmosphere at room temperature for 5 h only using potassium thioacetate as an odorless sulfur source and a base simultaneously.